Teaching Complex Introductory Concepts in a Sophomore Circuits Course: A Descriptive Case Study - Nicole Pitterson (MDPI AG, 2023)
This descriptive case study explores the teaching and learning of complex introductory circuit concepts in a compulsory sophomore circuits' course. The study investigates the instructional strategies employed by the instructor to facilitate students' understanding of intricate circuit phenomena. Data were collected through classroom observations, interviews with the instructor, and an analysis of the course documents. The findings shed light on the challenges encountered by students when grappling with introductory circuit concepts, the effectiveness of different instructional methods, and implications for curriculum design and pedagogical approaches in electrical engineering education. Specifically, the instructors reported students' prior knowledge, the nature of the content, and the structure of the course itself as some of the main features that impact students' overall learning of the content. The study highlights the importance of providing targeted support and scaffolding to students, promoting active learning strategies, and incorporating practical applications to enhance the comprehension of introductory circuit concepts in sophomore-level electrical engineering courses.